Training on Making Geography Problems Using Taxonomy of Spatial Thinking - Syafrida Selafiardy; Irfan Rifani; Noova Jans Ester Mengko (CV. TOTUS TUUS, 2024)
Community service activities about training in making geography problems usingtaxonomy of spatial thinking at the high school education level are based on the lack of implementation of taxonomy of spatial thinking in the learning implementation plan and test problems. This makes the analysis of problem solving low, whereas the analysis of problem solving is the spatial ability of geography. This activity is not limited to training in making geography problems only, but also the application of spatial thinking problems up to evaluation and follow-up how the process has been done. In addition, the science and technology used to support this activity is the activity team will evaluate the problems commonly used by teachers at the time of the test, to then analyze how far the problems contain taxonomy of spatial thinking.